Biochemical, genomic and structural characteristics of the Acr3 pump in Exiguobacterium strains isolated from arsenic-rich Salar de Huasco sediments - Castro-Severyn, Juan; Pardo-Esté, Coral; Araya-Durán, Ingrid; Gariazzo, Valentina; Cabezas, Carolina; Valdés, Jorge; Remonsellez, Francisco; Saavedra, Claudia P. (Frontiers in Microbiology, 2022)
Arsenic is a highly toxic metalloid of major concern for public safety. However, microorganisms have several resistance mechanisms, particularly the expression of arsenic pumps is a critical component for bacterial ability to expel it and decrease intracellular toxicity. In this study, we aimed to characterize the biochemical, structural, and genomic characteristics of the Acr3 pump among a group of Exiguobacterium strains isolated from different sites of the arsenic-rich Salar de Huasco (SH) ecosystem. We also determined whether the differences in As(III) resistance levels presented by the strains could be attributed to changes in the sequence or structure of this protein. In this context, we found that based on acr3 sequences the strains isolated from the SH grouped together phylogenetically, even though clustering based on gene sequence identity did not reflect the strain´s geographical origin. Furthermore, we determined the genetic context of the acr3 sequences and found that there are two versions of the organization of acr3 gene clusters, that do not reflect the strain’s origin nor arsenic resistance level. We also contribute to the knowledge regarding structure of the Acr3 protein and its possible implications on the functionality of the pump, finding that although important and conserved components of this family of proteins are present, there are several changes in the amino acidic sequences that may affect the interactions among amino acids in the 3D model, which in fact are evidenced as changes in the structure and residues contacts. Finally, we demonstrated through heterologous expression that the Exiguobacterium Acr3 pump does indeed improve the organisms As resistance level, as evidenced in the complemented E. coli strains. The understanding of arsenic detoxification processes in prokaryotes has vast biotechnological potential and it can also provide a lot of information to understand the processes of evolutionary adaptation.